Caracterização molecular, citogenética e fenotípica de acessos do Complexo Saccharum para fins de introgressão genética - Melloni, Maria Natália Guindalini [UNESP] (2014)
The growing demand for ethanol fuel as a renewable source of energy brings several new challenges to the breeding programs, since aside to the productivity increase there is a need to develop new sugarcane cultivars with high biomass production to be used in electricity production and cellulosic ethanol from second generation. The introduction of wild germplasm as a source of new genes for fiber, tillering among others constitutes one of the strategies to promote significant increases in biomass. Therefore, it is of imperative importance to characterize the basic germplasm composed by sugarcane wild accessions focusing on their use as parents in crosses. This project had as objective the characterization at the agronomic, cytogenetic and molecular level of accessions from the Saccharum Complex. The biometric and quality atrtributes of the wild accessions were evaluate at field experiments. The magnitude of the genetic variability of the wild accessions and commercial cultivars used as parents in the IAC genetic introgression program were obtain through microsatellite molecular markers. In addition, commercial varieties, cytotypes of S.spontaneum and hybrids selected from families derived from crosses between cultivars and wild accessions were characterizing by cytogenetic techniques. The obtained results will give support to the Genetic Introgression Program from the IAC Sugarcane Breeding Program in the development of high biomass cultivars